Research on urban teacher learning : examining contextual factors over time - Stairs, Andrea J.; Donnell, Kelly A. (Emerald Publishing Limited : IAP-Information Age Publishing, Inc., 2010)
This book presents a range of evidence-based analyses focused on the role of contextual factors on urban teacher learning. Part I introduces the reader to the conceptual and empirical literature on urban teacher learning. Part II shares eight research studies that examine how, what, and why urban teachers learn in the form of rich longitudinal studies. Part III analyzes the ways federal, state, and local policies affect urban teacher learning and highlights the synergistic relationship between urban teacher learning and context. What makes this collection powerful is not only that it moves research front and center in discussions of urban teacher learning, but also that it recognizes the importance of learning over time and the way urban schools' contexts and conditions enable and constrain teacher learning.